The Long-Run Spillover Effects of Pollution: How Exposure to Lead Affects Everyone in the Classroom - Gazze, Ludovica; Persico, Claudia; Spirovska, Sandra (Journal of Labor Economics, 2024)
Children exposed to pollutants like lead have lower academic achievement and are more likely to engage in risky behavior. However, little is known about whether lead-exposed children affect the long-run outcomes of their peers. We estimate these spillover effects using unique data on preschool blood lead levels (BLLs) matched to education data for all students in North Carolina public schools. We compare siblings whose school-grade cohorts differ in the proportion of children with elevated BLLs, holding constant school and peers’ demographics. Having more lead-exposed peers is associated with lower high school graduation and SAT-taking rates and increased suspensions and absences.